Identification of ESM1 as a Potential Biomarker Involving Drug Sensitivity and the Tumor Immune Microenvironment that Promotes Proliferation of Melanoma: ESM1 as a Potential Biomarker in Proliferation of Melanoma - Wang, Miaomiao; Ge, Hongfen; Liang, Shuya; Chen, Guanzhi (Cellular and Molecular Biology, 2023)
ESM1 may play a role in human cancers, but its role in melanoma remains unclear. This study investigated ESM1 expression in Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) databases and confirmed it through immunohistochemistry (IHC) and Western blotting (WB). Using the ESM1 gene expression levels, we divided TCGA samples into high and low-expression groups and identified differentially expressed genes (DEGs) between them. We then performed GO and KEGG enrichment analyses on these DEGs and explored the immune landscape while identifying anti-tumor drugs. ESM1 was found to be highly expressed in metastatic melanoma compared to primary melanoma and normal tissues. This was associated with increased numbers of immune-related cells and genes, as well as the activation of tumor progression pathways such as Notch and Wnt. In the high ESM1 expression group, the number of multiple immune-related cells and the expression of immune-related genes correlated with the presentation of ESM1, as well as the agonism of pathways related to tumor progressions. Immunohistochemistry and WB demonstrated a significant increase in ESM1 expression in metastatic lesions. Multiple GEO datasets showed higher ESM1 mRNA expression in malignant melanoma than in other benign tumors. ESM1 knockdown in a mouse model reduced tumor volume and weight related to the Wnt/-catenin and NOTCH signaling pathways. So, ESM1 is a promising biomarker for drug sensitivity, the tumor immune microenvironment, and the proliferation of cutaneous melanoma.